2022
DOI: 10.18332/tid/146960
|View full text |Cite
|
Sign up to set email alerts
|

School tobacco-related curriculum and behavioral factors associated with cigarette smoking among school-going adolescents in Zambia: Results from the 2011 GYTS study

Abstract: INTRODUCTION Tobacco smoking is a global public health concern. It has been projected that children and young people who are alive today in developing countries will bear the most burden of tobacco-related morbidity and mortality in the near future. This study investigated the school tobacco-related curriculum and behavioral factors associated with cigarette smoking among school-going adolescents. METHODS We accessed secondary data in a public domain collected using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
(32 reference statements)
2
5
0
Order By: Relevance
“…As shown by the results of this study, of those who participated in the STEPS survey, 11.0% reported being current tobacco smokers. These findings are consistent with the previous surveys that have shown a national range of 6.8% to 11.89% (Cosmas, 2022;Nyirenda et al, 2019;Olowski P, 2016;S, 2009;Zulu R, 2008). Our estimate is slightly lower than what has been reported in other countries (Dickson et al, 2017), yet it remains notably higher than the tobacco smoking prevalence found in other sub-Saharan countries (Guliani et al, 2019;He et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…As shown by the results of this study, of those who participated in the STEPS survey, 11.0% reported being current tobacco smokers. These findings are consistent with the previous surveys that have shown a national range of 6.8% to 11.89% (Cosmas, 2022;Nyirenda et al, 2019;Olowski P, 2016;S, 2009;Zulu R, 2008). Our estimate is slightly lower than what has been reported in other countries (Dickson et al, 2017), yet it remains notably higher than the tobacco smoking prevalence found in other sub-Saharan countries (Guliani et al, 2019;He et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…This study shows that the prevalence of tobacco smoking in Zambia is of a public health concern and compared with previous national surveys; there has not been a significant overall reduction (Cosmas, 2022;Nyirenda et al, 2019;Olowski, 2016;S, 2009;Zulu, 2008) showing that there is need for implementation of interventions that impact behaviour change. As shown by the results of this study, of those who participated in the STEPS survey, 11.0% reported being current tobacco smokers.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations